PENGEMBANGAN EKOWISATA SUBAK SEMBUNG DENGAN RANCANGAN JOGGING TRACK BERINOVASI ECO PAVING DARI LIMBAH DAUR ULANG PLASTIK - Mumpuni, S.C.; Putra, I.N.A.P.; Karunia, K.T.A.; Pramana, I.G.N.D.A.; Putra, P.B.W.; Saraswati, A.A.A.O. (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i06.p14, 2024)
Waste is a problem that is still difficult to deal with by most people, including plastic waste in Peguyangan Village. Plastic is a material that is quite difficult to decompose so innovation is needed to overcome these problems. Therefore, the innovation of using plastic waste as a pavement for jogging tracks in the Subak Sembung area is suitable, this is one of the problem solving considering that the jogging track infrastructure in Subak Sembung has begun to be damaged and less attention. The road pavement utilizes plastic as a substitute for fine aggregate where the road pavement has strength, water absorption, and also wear resistance based on Indonesian National Standards.